2016
DOI: 10.1021/acs.molpharmaceut.6b00633
|View full text |Cite
|
Sign up to set email alerts
|

Light Control of Insulin Release and Blood Glucose Using an Injectable Photoactivated Depot

Abstract: In this work we demonstrate that blood glucose can be controlled remotely through light stimulated release of insulin from an injected cutaneous depot. Human insulin was tethered to an insoluble but injectable polymer via a linker, which was based on the light cleavable di-methoxy nitrophenyl ethyl (DMNPE) group. This material was injected into the skin of streptozotocin-treated diabetic rats. We observed insulin being released into the bloodstream after a 2 min trans-cutaneous irradiation of this site by a co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
32
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 28 publications
(32 citation statements)
references
References 32 publications
0
32
0
Order By: Relevance
“…It has been demonstrated for several proteins that physical crosslinking to gel matrices can minimally impact biological activity, and may result in somewhat decreased activity for TEM1 released from Ru‐hydrogels (Figure S8).…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…It has been demonstrated for several proteins that physical crosslinking to gel matrices can minimally impact biological activity, and may result in somewhat decreased activity for TEM1 released from Ru‐hydrogels (Figure S8).…”
Section: Figurementioning
confidence: 99%
“…These experiments confirmed that light exposure modulates release, enabling consistents tep-wise dosing of an active protein from Ru-hydrogelv ia light-mediated surface erosion. Because one RuAldehydel igand is exchanged, TEM1 protein released from the hydrogel wasm odified with residual ruthenium complex as Ru(bpy) 2 It has been demonstrated for several proteins that physical crosslinking to gel matrices can minimally impact biological activity, [41,42] andm ay result in somewhat decreased activity for TEM1 released from Ru-hydrogels ( Figure S8).…”
mentioning
confidence: 99%
“…[133] Conjugating insulin proteins to a biodegradable insoluble matrix via a photolabile linker enabled light controlled release of insulin in an in vivo mouse model. [134] This application of light-controlled release has the potential to be applied to numerous other drugs in which spatiotemporal delivery is advantageous for treatment. While incorporation of caging groups directly into proteins has afforded investigation of many biological processes, light-responsive motifs cannot be genetically inserted into nucleic acids and thus require synthetic approaches.…”
Section: Methodsmentioning
confidence: 99%
“…This supposition is also supported by tissue phantom studies performed here, showing efficient light-induced de-repression at subdermal depths of as high as 1 mm, sufficient in many instances for activation within human superficial veins as well as within transcutaneous or some transepithelial disease sites. 24 Others have also demonstrated that structurally related photocages appended to solid implants can be transcutaneously photoactivated in mice, 28,29 thus we are optimistic regarding future in vivo feasibility.…”
Section: P R E P R I N T C O P Ymentioning
confidence: 99%